2011
DOI: 10.2298/tsci110225049a
|View full text |Cite
|
Sign up to set email alerts
|

Comparative thermodynamic analysis of dual cycle under alternative conditions

Abstract: In this paper, finite-time thermodynamic analysis of an air-standard internal-combustion Dual cycle is performed. Maximum power (MP), maximum power density (MPD), maximum efficient power (MEP) which are three alternative performance criteria are derived. The effects of the design parameters such as volume ratio and extreme temperature ratio of the cycle have been investigated under MP, MPD and MEP conditions. The analyzed results of air-standard internal-combustion Dual cycle showed the design parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Atmaca et al [197] investigated the efficient power characteristic of a reversible Dual cycle, examined the influences of design parameters (including volume ratio and extreme temperature ratio) on cycle performance under MP, MPD, MEP and ME conditions, and found that the design parameters under MEP condition were better than those under MP and MPD conditions. Blank and Wu [198] obtained the relation of the optimum CR varied with the cycle maximum temperature of an endoreversible Dual cycle when the work output was the maximum, and found that the optimum CR would increase when the cycle maximum temperature increased and would be not influenced by fuel-air mass ratio.…”
Section: The Progress In Optimum Performance Studies For As Dual Cyclesmentioning
confidence: 99%
“…Atmaca et al [197] investigated the efficient power characteristic of a reversible Dual cycle, examined the influences of design parameters (including volume ratio and extreme temperature ratio) on cycle performance under MP, MPD, MEP and ME conditions, and found that the design parameters under MEP condition were better than those under MP and MPD conditions. Blank and Wu [198] obtained the relation of the optimum CR varied with the cycle maximum temperature of an endoreversible Dual cycle when the work output was the maximum, and found that the optimum CR would increase when the cycle maximum temperature increased and would be not influenced by fuel-air mass ratio.…”
Section: The Progress In Optimum Performance Studies For As Dual Cyclesmentioning
confidence: 99%
“…For this purpose, Sahin et al [13] has proposed the power density criteria addressing the system dimensions and performance within the constraints of the first law of thermodynamics and defined as the ratio of the power generated to the maximum volume in a Brayton cycle. However, optimization indicative of the maximization of this function have been performed for such power cycles as the Carnot [14][15][16], Brayton [17][18][19][20][21], dual [22,23], Atkinson [24,25], and diesel [26] systems in recent years. Studies have investigated the effects design and irreversibility parameters have on performance criteria.…”
Section: Introductionmentioning
confidence: 99%
“…)= a +a T+a T +a T +a T R  (23) Net power is found by subtracting the power generated in the turbine from the power consumed in the compressor: efficiency is calculated from the following equation:net in η=W /Q (24) Exergy is obtained with the physical exergy, chemical exergy, kinetic exergy and potential exergy. Kinetic exergy and potential exergy are assumed to be negligible.…”
mentioning
confidence: 99%